Welcome to the Arena: An Introduction to the Special Issue on Power and Politics in Sport - Marshall J. Magnusen; Samuel Y. Todd (Journal of Applied Sports Management, 2016)
Organizational politics is about influence and those who influence. From Fortune 500 companies to startups and from high school athletic departments to professional sport organizations, power and organizational politics are an entrenched component of nearly all work settings. Because they are social systems, organizations tend to be political as members compete for limited resources in order to accomplish work objectives and get ahead. As such, organizational members who have an ability to influence others in order to achieve a desired objective are said to have “political skill.” This ability, scholars note, takes several dimensions: (1) social astuteness: interpreting social situations and having the savvy to generate an effective response, (2) interpersonal influence: developing good rapport with people to build trust, (3) networking ability: developing connections with influential people for future gain, and (4) apparent sincerity: showing, or appearing to show genuine interest in others.